The Effect of Investment Decisions and Working Capital on Firm Value - Heru Harmadi Sudibyo (ProBisnis : Jurnal Manajemen, 2023)
The purpose of research and compiling this thesis is to analyze and determine the effect of investment decisions and working capital on firm value (Y) in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The population in this study are food and beverage companies, a total of 26 companies. Sampling and purposive sampling in order to obtain a sample of 8 food and beverage companies. Data collection was carried out by multiple linear regression analysis. The results of this study indicate that investment decisions have no effect on firm value, while working capital has a significant effect on firm value, and the simultaneous results with investment decisions and working capital have a simultaneous effect on firm value.